Nursing consultation: a concept analysis - Pimentel-Jaimes, José Alfredo (Universidad de Sonora, 2019)
Introduction: Nursing consultation has always existed within the public or private domain, inside and outside hospitals, and at all levels of care; however, it has rarely been implemented in a systematic way or with this name. Objective: Analyze the concept of nursing consultation. Methodology: This analysis was carried out following the methodology developed by Walker and Avant, through which the characteristics that define a concept and its attributes are discussed. Results: This analysis suggests that the nursing consultation can be seen as a technical, scientific, free, and autonomous service that is granted by nursing professionals, either in the public or private domain, inside and outside hospitals, and in all levels of health care. Its main purpose is to promote, enable, include, prevent, detect, and solve health needs and problems of the individual, family, and community in all stages of life. Conclusions: The importance of the nursing consultation lies in three main aspects: 1) it allows individual, family, and community health needs and problems to be solved in all stages of life; 2) for nursing professionals it works as the access door towards professional autonomy, independent practice, and social recognition; and 3) it represents an extension of the arm of the national health system (public or private), as it increases access to health and universal health coverage.